Nursing Care: A Combination of Occupational Therapy and Psycho-Religious Therapy for Changes in Hallucination Symptoms in Schizophrenia Patients at Nur Ilahi Rehabilitation Clinic - Iyus Yosep; Annisa Aulia Husna; Nur Oktavia Hidayati (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: Schizophrenia is a mental disorder that causes hallucinations, delusions, and highly disorganized thinking and behavior that impairs daily functioning, and can be disabling. 90% of people with schizophrenia have hallucinations. This study aimed to determine the effectiveness of occupational therapy and psychoreligious therapy in reducing hallucinations. Objective: This study was to determine the effectiveness of occupational therapy and psychoreligious therapy in reducing hallucinations. Methode : This study used a case study with a nursing care approach that includes assessment to evaluation. Patients with auditory hallucinations were given occupational therapy to shift focus and psycho-religious therapy to provide relaxation for hallucinatory patients. This therapy was given for 10 days with a total of 5 meetings. Results: Problems with sensory perceptual disturbances: reduced auditory hallucinations. Patient get a combination of occupational therapy and psycho-religious therapy which shows changes in behavior such as clients being able to control hallucinations and taking part in activities held by the clinic. This can be seen from the client being able to control his hallucinations, the frequency of hallucinations is reduced, and the client regularly participates in activities held by the clinic. Conclusion: Occupational therapy and psycho-religious therapy can be used for patients with hallucinatory disorders.  Therapy is only carried out for 10 days to the patient. so the recommendation for further research is the need to analyze the effectiveness of occupational therapy and psycho-religious therapy to reduce the symptoms of auditory hallucinations. Nursing Implications: This research was conducted to become a basis for nurses in carrying out nursing interventions in patients with sensory perception disorders: auditory hallucinations and can be a guideline for health facilities to make policies regarding interventions for clients with auditory hallucinations.